The predictive and incremental validity of two self-report risk assessment measures with adult male oOffenders who have mental health problems - Rodrigues, Nicole C. (Criminal justice and behavior, 2016)
We examined the predictive and incremental validity of two self-report risk assessment measures?the Self-Appraisal Questionnaire (SAQ) and the Measure of Criminal Attitudes and Associates (MCAA)?in a sample of 121 adult male offenders, with mental health problems in a correctional treatment setting. Both the SAQ and MCAA were significantly and positively correlated with a standard risk/need assessment currently used in corrections, the Level of Service Inventory?Ontario Revision (LSI-OR). All three risk measures significantly predicted general recidivism within 1 year of follow-up. The SAQ and LSI-OR also significantly predicted institutional incidents (threat, verbal aggression, or assault). In addition, the MCAA significantly added to the prediction of general recidivism provided by the LSI-OR, whereas the SAQ did not, likely reflecting the relatively high content overlap of the SAQ and LSI-OR. Neither self-report measure added to the ability of the LSI-OR to predict institutional incidents involving aggression.